2016
DOI: 10.1007/s11523-016-0432-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Ran GTPase Components Regulating Nuclear Export, but not Mitotic Spindle Assembly, Marks Chromosome Instability and Poor Prognosis in Breast Cancer

Abstract: We find that overexpression of Ran GTPase components involved in nuclear export, but not nuclear import or mitotic spindle assembly, is a strong CIN-associated marker for poor breast cancer prognosis. This could mean that increased nuclear export (of, for instance, pRb, p53, p73, BRCA1, p21, p27, E2F4, IκB, survivin), rather than spindle defects, mainly drives CIN and tumorigenesis. Hence, selective inhibitors of nuclear export may be effective for treating the most aggressive and chromosomally unstable breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 60 publications
4
44
0
Order By: Relevance
“…In an effort to independently validate these results, we used a combination of 28 other microarray datasets, as described [19, 20]. However, this showed that COL4A1 expression did not significantly change (1.15-fold increase, p  = 0.2574, t test, n  = 1137) and that COL4A2 expression was significantly reduced (1.53-fold decrease, p  = 7.97 × 10 −10 , n  = 2830), rather than increased (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an effort to independently validate these results, we used a combination of 28 other microarray datasets, as described [19, 20]. However, this showed that COL4A1 expression did not significantly change (1.15-fold increase, p  = 0.2574, t test, n  = 1137) and that COL4A2 expression was significantly reduced (1.53-fold decrease, p  = 7.97 × 10 −10 , n  = 2830), rather than increased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…and the Nottingham Prognostic Index, were performed as described [17, 18]. Survival analyses were performed using a single clinical feature at a time, i.e., distant metastasis-free survival, recurrence-free survival, or overall survival, and by splitting the gene expression in tumors into below (low) and above (high) the median expression level, as described [19, 39]. Statistical analyses were performed using log-rank Mantel-Cox tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no comprehensive studies have been performed in CRC, limited evidence in previous studies has observed overexpression of XPO5 in urothelial (10) and breast cancer (11, 12). Another recent study showed that XPO5 is a critical regulator of cell cycle (13).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated expression of XPOT is associated with cell proliferation in human promyelocytic leukemia . Overexpression of XPOT leads to more aggressive and chromosomally unstable breast cancers . However, the role of XPOT in HCC has not been studied before.…”
Section: Discussionmentioning
confidence: 99%